Ten years later: a review of the US 2009 institute of medicine report on conflicts of interest and solutions for further reform. Issue 1 (11th November 2020) - Torgerson, Trevor; Wayant, Cole; Cosgrove, Lisa; Akl, Elie A; Checketts, Jake; Dal Re, Rafael; Gill, Jennifer; Grover, Samir C; Khan, Nasim; Khan, Rishad; Marušić, Ana; McCoy, Matthew S; et al.
Abstract : Conflicts of interest (COIs) in healthcare are increasingly discussed in the literature, yet these relationships continue to influence healthcare. Research has consistently shown that financial COIs shape prescribing practices, medical education and guideline recommendations. In 2009, the Institute of Medicine (IOM, now the National Academy of Medicine) published Conflicts of Interest in Medical Research, Practice, and Education —one of the most comprehensive reviews of empirical research on COIs in medicine. Ten years after publication of theIOM's report, we review the current state of COIs within medicine. We also provide specific recommendations for enhancing scientific integrity in medical research, practice, education and editorial practices.